The Form of Daily Use in Language (Javanese Language Dialect) on Early Children Age 5-6 Years - Krisnaningrum, Dwi; Sularti Dewanti Handayani, Sri (BELIA: Early Childhood Education Papers, 2020)
Daily forms of language use, especially the Javanese dialect in early childhood, have diversity between one child and another. It is influenced by differences in the backgrounds in which they live. As in the use of the sentences, "kae ana batihe dhewe (there is brother)", "piye leh? (how ?)", The use of the words with the local dialect has a difference with the dialect used in the community in other regions. So, the researcher wants to know some forms of Javanese dialect that are used in the Samin tribe community, especially by early childhood aged 5-6 years. This study aims to describe what forms of language use, namely the Javanese dialect used by early childhood aged 5-6 years in the Samin Blora tribe community. The research method uses a qualitative approach to the type of ethnographic research. Data collection techniques used is interviews, observation, and documentation. Research subjects are early childhood aged 5-6 years, parents, educators, and Samin tribe chief. The data analysis method used is to use a form of analysis by Miles and Huberman which consists of several stages. The results show that the use of the Javanese dialect in early childhood aged 5-6 years in the Samin tribe community is one form of protecting the nation's next-generation through language. The use of the Javanese dialect is used in everyday interactions and communication of early childhood to the interlocutors, namely parents, educators, neighbors, and peers with the Javanese dialect form commonly used which is the Ngoko Javanese. Some of the dialect forms used in the Samin tribe community, namely early childhood use a form of phonetic change from "Uh" to "Eh", change from "Uh" to "Oh", the use of "-em" affixes, and the use of "re" additions and "leh" in a few sentences in a conversation carried out by early childhood in the Samin tribe community. The factors that support children in the use of the Javanese dialect are the family environment where the child lives because it is an important subject that influences the use of one's language, especially early childhood, and the environmental factors of the community where the child lives in the habit of the majority of the community in using dialect Javanese can also be a dominant factor for children's language use.